2014
DOI: 10.3389/fmicb.2014.00247
|View full text |Cite
|
Sign up to set email alerts
|

Connecting lignin-degradation pathway with pre-treatment inhibitor sensitivity of Cupriavidus necator

Abstract: To produce lignocellulosic biofuels economically, the complete release of monomers from the plant cell wall components, cellulose, hemicellulose, and lignin, through pre-treatment and hydrolysis (both enzymatic and chemical), and the efficient utilization of these monomers as carbon sources, is crucial. In addition, the identification and development of robust microbial biofuel production strains that can tolerate the toxic compounds generated during pre-treatment and hydrolysis is also essential. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…First, efforts have focused on understanding the toxic compounds in the hydrolysate as well as the effect of these toxic compounds on various host microorganisms. It was found that acetate, furfural and phenolic aldehydes are the major identifiable inhibitory compounds in the hydrolysate of pretreated biomass for Z. mobilis (Franden et al ., , ; Wang et al ., ; Gu et al ., ; Yi et al ., ). However, phenolic acids (such as ferulic acid and p ‐coumaric acid) and their amides are the most abundant inhibitor in AFEX‐pretreated corn stover and switchgrass (Keating et al ., ; Serate et al ., ).…”
Section: Inhibitors and Microbial Robustness Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…First, efforts have focused on understanding the toxic compounds in the hydrolysate as well as the effect of these toxic compounds on various host microorganisms. It was found that acetate, furfural and phenolic aldehydes are the major identifiable inhibitory compounds in the hydrolysate of pretreated biomass for Z. mobilis (Franden et al ., , ; Wang et al ., ; Gu et al ., ; Yi et al ., ). However, phenolic acids (such as ferulic acid and p ‐coumaric acid) and their amides are the most abundant inhibitor in AFEX‐pretreated corn stover and switchgrass (Keating et al ., ; Serate et al ., ).…”
Section: Inhibitors and Microbial Robustness Developmentmentioning
confidence: 97%
“…However, inhibitory compounds formed during this process, including furfural, hydroxymethylfurfural (HMF), formic acid, levulinic acids, acetic acid, vanillin and phenolic aldehydes, have negative effects on cellular growth, metabolism and the production of desired products (Delgenes et al ., ; Gu et al ., ; Yi et al ., ; Park et al ., ). Detailed work has been conducted to investigate the composition of hydrolysate to find inhibitory compounds, and a high‐throughput biological growth assay has been developed to obtain detailed inhibitory kinetics for individual compounds or synergistic combinations of these compounds (Franden et al ., , ; Wang et al ., ; Yi et al ., ).…”
Section: Inhibitors and Microbial Robustness Developmentmentioning
confidence: 99%
“…CY-1 did not accumulate PHB with compounds like 4-BP, 4-s-BP, 4-NP, and phenanthrene. 32 Mozumder et al and Garcia-Gonzalez et al reported 62% and 61% PHB production with C. necator DSM 545 using waste glycerol and CO 2 as substrates respectively. 29 This is a possible reflection on the metabolic routes employed in the breakdown of these substrates and also the substrate range and efficiency of the PHB polymerase.…”
Section: Phb Productionmentioning
confidence: 99%
“…The major components of glucose, xylose, arabinose, acetic acid, and furans, as well as a wide variety of aliphatic acid compounds can be detected directly from hydrolysate samples by highperformance liquid chromatography (HPLC) or gas chromatography (GC) using different columns and detectors (Franden et al 2013;Gu et al 2014). Minor components, especially for phenolic compounds, have been extracted from hydrolysate using organic solvents, concentrated by evaporation, and analyzed by gas chromatographymass spectrometer (GC-MS), liquid chromatographymass spectrometer (LC-MS), and/or inductively coupled plasma mass spectrometer (ICP-MS) (Gu et al 2014;Wang et al 2014). Inductively coupled plasma optical emission spectrometry (ICP-OES) has also been used for inorganic ion analysis and many different mineral elements such as magnesium, potassium, manganese, iron, copper, and calcium have been identified in lignocellulosic hydrolysates (Jin et al 2013;Le et al 2014).…”
Section: Identification and Quantification Of Inhibitors In Lignocellmentioning
confidence: 99%